Cigarette smoke extract alters genome‐wide profiles of circular RNAs and mRNAs in primary human small airway epithelial cells. Issue 8 (29th May 2019) - Zeng, Ni; Wang, Tao; Chen, Mei; Yuan, Zhicheng; Qin, Jiangyue; Wu, Yanqiu; Gao, Lijuan; Shen, Yongchun; Chen, Lei; Wen, Fuqiang
Abstract: As a novel kind of non‐coding RNA, circular RNAs (circRNAs) were involved in various biological processes. However, the role of circRNAs in the developmental process of chronic obstructive pulmonary disease (COPD) is still unclear. In the present study, by using a cell model of COPD in primary human small airway epithelial cells (HSAECs) treated with or without cigarette smoke extract (CSE), we uncovered 4, 379 previously unknown circRNAs in human cells and 903 smoke‐specific circRNAs, with the help of RNA‐sequencing and bioinformatic analysis. Moreover, 3, 872 up‐ and 4, 425 down‐regulated mRNAs were also identified under CSE stimulation. Furthermore, a putative circRNA‐microRNA‐mRNA network was constructed for in‐depth mechanism exploration, which indicated that differentially expressed circRNAs could influence expression of some key genes that participate in response to pentose phosphate pathway, ATP‐binding cassette (ABC) transporters, glycosaminoglycan biosynthesis pathway and cancer‐related pathways. Our research indicated that cigarette smoke had an influence on the biogenesis of circRNAs and mRNAs. CircRNAs might be involved in the response to CSE in COPD through the circRNA‐mediated ceRNA networks.